Kinins and Kinin Receptors in Cardiovascular and Renal Diseases - Jean-Pierre Girolami; Nadine Bouby; Christine Richer-Giudicelli; Francois Alhenc-Gelas (MDPI AG, 2021)
This review addresses the physiological role of the kallikrein-kinin system in arteries, heart and kidney and the consequences of kallikrein and kinin actions in diseases affecting these organs, especially ischemic and diabetic diseases. Emphasis is put on pharmacological and genetic studies targeting kallikrein; ACE/kininase II; and the two kinin receptors, B1 (B1R) and B2 (B2R), distinguished through the work of Domenico Regoli and his collaborators. Potential therapeutic interest and limitations of the pharmacological manipulation of B1R or B2R activity in cardiovascular and renal diseases are discussed. This discussion addresses either the activation or inhibition of these receptors, based on recent clinical and experimental studies.